2013
DOI: 10.1111/plb.12053
|View full text |Cite
|
Sign up to set email alerts
|

Physiological aspects of raffinose family oligosaccharides in plants: protection against abiotic stress

Abstract: Abiotic stresses resulting from water deficit, high salinity or periods of drought adversely affect plant growth and development and represent major selective forces during plant evolution. The raffinose family oligosaccharides (RFOs) are synthesised from sucrose by the subsequent addition of activated galactinol moieties donated by galactinol. RFOs are characterised as compatible solutes involved in stress tolerance defence mechanisms, although evidence also suggests that they act as antioxidants, are part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
201
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(214 citation statements)
references
References 105 publications
10
201
0
3
Order By: Relevance
“…Raffinose showed a pattern similar to that of the TCH, peaking after the first 12 h of stress exposure. This sugar has been suggested to be associated with stress tolerance, defense mechanisms, and carbon partitioning in the cell, serving as an antioxidant signaling stress (64). These observations indicate that as long as Chl content is relatively high (9 -12 mg liter ÏȘ1 ), the cell devotes its energy and carbon reserves to maintaining a carbon pool in the form of free sugars and starch.…”
Section: Discussionmentioning
confidence: 69%
“…Raffinose showed a pattern similar to that of the TCH, peaking after the first 12 h of stress exposure. This sugar has been suggested to be associated with stress tolerance, defense mechanisms, and carbon partitioning in the cell, serving as an antioxidant signaling stress (64). These observations indicate that as long as Chl content is relatively high (9 -12 mg liter ÏȘ1 ), the cell devotes its energy and carbon reserves to maintaining a carbon pool in the form of free sugars and starch.…”
Section: Discussionmentioning
confidence: 69%
“…Raffinose and other members of the raffinose family oligosaccharides are involved in stress tolerance and act as antioxidants. Furthermore, raffinose family oligosaccharides are part of the carbon storage system (ElSayed et al, 2014), possibly explaining why SIP2 is downregulated. The other four core response genes are involved in the synthesis of wax esters (FOLDED PETAL1) (Takeda et al, 2013), primary metabolism (PHOSPHOENOLPYRUVATE CARBOXYLASE KINASE1), stress-induced chloroplast disruption (CHLOROPLAST VESICULATION) (Wang and Blumwald, 2014), and Zn/Fe transport (IRON REGULATED TRANSPORTER3).…”
Section: Predictive Genes For Mild Drought In Growing Leavesmentioning
confidence: 99%
“…It has been demonstrated that certain sugars (such as Suc, Tre, and Raf) play a central role in the protection from drought stress in a wide range of organisms by helping to maintain the structure of the cytoplasm and to stabilize certain proteins when the amount of water is reduced (for review, see Ingram and Bartels, 1996). Galactinol, which increased up to 2.3-fold and is used for Raf synthesis, also plays an important role in abiotic stress tolerance (Elsayed et al, 2014). The higher levels of sugars in SSE seeds are apparently not the result of starch degradation, since the levels of starch increased in these seeds.…”
Section: High Expression Levels Of Atd-cgs Induce Typical Stress-assomentioning
confidence: 99%